Slow Living Financial Behavior: Mindful Consumption, Entrepreneurial Transition, and Sustainable Lifestyles - Lukmana Putra, Indra (Lembaga Riset Penelitian dan PKM Aliansi Manajemen Indonesia, 2025)
Explores slow living financial behavior countercultural lifestyle rooted mindfulness, intentional financial planning, resistance to pervasive consumerism. Utilizing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and social media content analysis. An objects who individuals aged 35–40 who exited long-term corporate careers to pursue small, passion-driven enterprises, signaling a second stage behavioral financial life-cycle. Findings reveal professional dissatisfaction, burnout, and misalignment between effort how reward in traditional work environments. Slow living approach promotes a more sustainable meaningful life, requires substantial financial preparation, adaptation which entrepreneurial demands—areas where many practitioners initially lack readiness. Financial wellbeing emerges as a prerequisite lifestyle shifting, ensuring resilience during the transition. Finding highlights importance structural mechanisms cross-subsidization socially motivated investors to sustain micro-enterprises aligned slow living values. Ultimately, sustainable adoption slow living financial behavior depends on the interplay between conscious consumption, economic stability, and systemic support.